2021
DOI: 10.47626/2237-6089-2020-0129
|View full text |Cite
|
Sign up to set email alerts
|

Personal value, self-efficacy, and social acceptability of a social behavior as correlates of behavioral action in social anxiety

Abstract: Introduction Current therapies for social anxiety disorder emphasize taking behavioral action; active engagement of a behavior despite any present fear or anxiety that is associated with the behavior, through use of exposures. However, less is known about the mechanisms of behavioral action. The present study aimed to examine personal value, self-efficacy, and the perceived social acceptability of a social behavior as correlates of behavioral action in a high social anxiety sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…While most research focuses on problematic gamers, one recent study comparing patients with IGD, gamers, and nongamers found that gamers had significantly lower self‐efficacy than nongamers 38 . As low self‐efficacy is associated with many psychiatric disorders, such as social anxiety, 39 ADHD, 40 and depression, this may be the reason for this somewhat high prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most research focuses on problematic gamers, one recent study comparing patients with IGD, gamers, and nongamers found that gamers had significantly lower self‐efficacy than nongamers 38 . As low self‐efficacy is associated with many psychiatric disorders, such as social anxiety, 39 ADHD, 40 and depression, this may be the reason for this somewhat high prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The somewhat high number of participants with mild social anxiety was probably the result of our study group being composed of general gamers and problematic gamers. Along with the low selfefficacy reported in gamers 38 and its correlation with social anxiety, 39 problematic gaming has also been shown to be a significant risk factor for IGD. 52 For a more in-depth analysis of the effect of comorbid disorders on IGD and GD, fixed effects of comorbidity and time on IGD and GD were analyzed.…”
Section: Discussionmentioning
confidence: 99%